Determinants of the development of multi-level marketing in Poland in the context of differences between generations X, Y, Z - Wadlewski, Aron -Axel (Serbian Journal of Management, 2022)
The main purpose of the article is an attempt to assess the development potential of Multi Level Marketing in Poland, considering differences in perception of the system by different generations. In the theoretical part of the article, the essence of the concept of Multi Level Marketing is explained, market trends in the development of direct selling are presented, and the characteristics of generations X, Y, and Z are described. Then, according to the empirical part of the paper, the results of surveys on the differences in the perception of Multi Level Marketing by Polish representatives of generations X, Y, and Z are presented. In the last part, based on the analysis of the collected data, conclusions were formulated concerning further development perspectives of the direct selling branch.
Keywords: multi-level marketing; network marketing; direct selling; generation X; generation Y; generation Z